2019
DOI: 10.1177/1758573218819828
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of shear wave elastography ultrasound to assess the supraspinatus tendon: An intra and inter-rater in vivo study

Abstract: Introduction Shear wave elastography ultrasound is a relatively new technique that evaluates the tissue elasticity by applying an acoustic radiation force impulse. It is undetermined how reliable this modality is in assessing rotator cuff tendons. The aim of this study, therefore, was to evaluate the reliability of shear wave elastography ultrasound to assess the stiffness of normal and tendinopathic supraspinatus tendons. Methods An inter- and intra-rater reliability trial was carried out using shear wave ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 19 publications
1
42
1
Order By: Relevance
“…Unfortunately, differentiating between these factors so that the underlying tissue material properties can be assessed remains challenging, which necessitates highly controlled testing conditions. Even so, SWE measurement reliability under in vivo conditions is typically low to moderate, 5 , 24 , 43 underscoring the sensitivity of SWE measurements to these factors and others (eg, anisotropy).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, differentiating between these factors so that the underlying tissue material properties can be assessed remains challenging, which necessitates highly controlled testing conditions. Even so, SWE measurement reliability under in vivo conditions is typically low to moderate, 5 , 24 , 43 underscoring the sensitivity of SWE measurements to these factors and others (eg, anisotropy).…”
Section: Discussionmentioning
confidence: 99%
“…A statistically significant difference was observed in their study between the two age groups, and SWE modulus showed a significant decrease in the over 60 years old age group. Hackett et al evaluated the reliability of SWE to evaluate the stiffness of normal and tendinopathic supraspinatus tendons (5). They assessed inter-and intra-rater reliability for performing SWE by three raters with different experiences in the conventional US and obtaining three readings in three different examinations per subject over a 1-week period.…”
Section: Resultsmentioning
confidence: 99%
“…This method measures the shear wave speed to evaluate mechanical properties of tissues to visualize tissue displacements to allow the examiner to infer information regarding the tissular biomechanics (1)(2)(3). Both methods are operator-dependent and have yielded favorable inter-rater reliability (4,5). This narrative review serves as an update on the novel literature concerning the usage of SE of the shoulder since 2018 until to date.…”
Section: Introductionmentioning
confidence: 99%
“…After an extensive literature search, several recently published studies were found that assessed the reliability estimates for elastography in different soft tissues structures, Ref. [17] including nerves [18], muscles [19], tendons [20,21] and arteries [22]. Features were assessed with quantitative elastography (including transverse velocity, transverse stiffness, cranio-caudal velocity and cranio-caudal stiffness, showing a poor repeatability of measurements with wide limits of agreement) and semi-quantitative elastography assessing SRs [8,9].…”
Section: Discussionmentioning
confidence: 99%